The meta-analysis study of SAVI learning model on student’s cognitive aspects in biology learning - Florentina Rahayu Esti Wahyuni; Wiro WIransah; Didin Syafruddin; Yakobus Bustami (STKIP Persada Khatulistiwa Sintang, 2022)
The meta-analysis study for currently do not have the latest research on the SAVI learning model on student’s cognitive aspect in learning biology, especially about education level, region, and the dependent variable. This research aims to analyze the effectiveness of apllication of the SAVI learning model on student’s cognitive aspects in Biology learning. The method used is meta-analysis, that is the analysis that present the results of publication scientific research in electronic journal nationally concern the influence of the SAVI learning model on student’s cognitive aspect. The sample used was 14 articles from 35 scientific articles published in accredited national journals, after filtering the articles. The instrument used is in the form of a category coding sheet for articles. The results showed that the overall results of SAVI learning model were able to improve the cognitive abilities of student in the experimental group with an effect size of 0.2246. Based on the education level at the elementary, junior, and senior high school levels with the effect size category, respectively obtained 0.2282, 0.1196, and 0.6162. Based on the region, the effect size in each region was obtained that is in Central Java 0.1389; East Java 0.2460; West Java 0.0394; Bali 0.3069; South Sumatra 0.0242, and 0.3057 in Southeast Sulawesi. Based on the research dependent variable with the results were obtained problem solving skill 0.0742; achievement 0.2916; critical thinking 0.1086; communication skill 0.0242; and reasoning ability 0.3057.